The effect of static stretch and dynamic range of motion training on the flexibility of the hamstring muscles - Brady, W. D.; Irion, J. M.; Briggler, M.
The purpose of the study was to compare the effects of DROM and static stretching of the hamstring muscles with a control group (performing no stretching activities) on increasing hamstring flexibility as measured by knee extension ROM. The null hypothesis to be tested is that if static stretch, DROM, and a control group are compared, no difference in knee extension ROM will occur following 6 weeks of training. Although the use of static stretch and DROM both resulted in an increase in hamstring flexibility (as determined by increased knee extension ROM), the results of the present study indicate that a 30-second static stretch was more effective than the DROM technique. Given that a 30- second static stretch performed one time per day over a 6-week period resulted in more than twice the gains in hamstring flexibility than performing DROM at the same frequency and duration, the use of DROM to effectively increase the flexibility of the hamstring muscle is in question.